types of fuzzy ideals in semigroups - Hadi, Rabee (University of Thi-Qar Journal of Science, 2008)
In this paper ,we study the notion of fuzzy ideal in semigroups and give some properties about it and we reviewed some types of ideals such as (regular,semiprime,(1,2)- ideal,(2,2)-ideal and gives some relationships between them.